Banality Leads to Trauma in Housewives: An Atlas of Impossible Longing by Anuradha Roy - S. Leena Devanesam, Dr. V. Manimozhi (International Journal of Advanced Science and Technology, 2020)
The housewives who endured symptoms of emotional disorder encountered difficult and challenging times, without exception they indicated that domestic life itself was the cause of emotional disorder that is termed as “terrible nerves.” Amulya, a learned family man left his family at Calcutta twenty years ago and settled down at Songarh town with his wife Kananbala and two sons Kamal and Nirmal, for his business’ sake. He was toiling the whole day to earn wealth whereas his wife, who is a homemaker, left alone not even with Indian neighbours, struggles and felt suppression of thoughts, feelings without exposure in later days, developed her as a traumatic person. This paper deals with a single house wife’s impact of displacement which made her lose family support and build with solidarity over time. This paper also limelights many thousands of wives who are entwined with traumatic problems which in due course becomes PTSD (Post Traumatic Stress Disorder).